The Functions of Language Analysis on Oral Tradition Tangis in Karonese - Ramayanti, Sri; Zainuddin, Zainuddin (TRANSFORM: Journal of English Language Teaching and Learning, 2022)
This research deals with the analysis of language functions on oral tradition's Tangis in Karonese. The aim of this research is to: (a) describe how language functions are realized on oral tradition's Tangis in Karonese and (b) explain the reason why language functions are used on oral tradition's Tangis in Karonese. This research was conducted by using the descriptive qualitative method. The data of this research is taken from the utterances spoken by the pilgrims when did the Tangis. There are five language functions found in Tangis from the six language functions proposed by Roman Jakobson. They were referential 54,1%, conative 32,4%, emotive 8,1%, phatic 2,7 %, and poetic 2,7%. Besides the language functions found, there are also the reasons the language functions are used on oral tradition's Tangis in Karonese. They were thoughts, feelings, needs, and observation.